Averaged modeling of PWM converters operating in discontinuous conduction mode. - Jian Sun (IEEE Transactions on power electronics)
Various aspects of averaged modeling of hard-switching pulse-width modulated (PWM) converters operating in the discontinuous conduction mode (DCM) are studied. A more streamlined modeling procedure is proposed which serves as a general framework for comparing different models. A duty ratio constraint that defines the diode conduction interval is identified to be the key to accurate prediction of high-frequency behavior. A new duty-ratio constraint is proposed that leads to full-order averaged models of DCM converters. Numerical analyses and experimental measurements confirm that the new models correctly predict the small-signal responses up to one third of the switching frequency and are more accurate than all previous models. Moreover, new analytical results are included to show the origin of the high-frequency pole in DCM operation and to explain why the full-order model is capable of accurately predicting it. Averaged circuit counterparts of the new models are developed in the form of averaged switch models to facilitate circuit simulation